Propagation of electromagnetic waves in weakly anisotropic media: Theory and applications - Kravtsov, Yury A.; Bieg, Bohdan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Quasi-isotropic approximation (QIA) of geometrical optics is outlined, which describes properties of electromagnetic waves in weakly anisotropic media, including weakly anisotropic fibers, liquid crystals and weakly magnetized plasma. QIA equations stem directly from the Maxwell equations and have the form of coupled differential equations of the first order for transverse components of the electromagnetic field. Being applied to magnetized plasma, QIA describes combined action of Faraday and Cotton–Mouton phenomena and serves as a theoretical background of plasma polarimetry in FIR and microwave bands.The coupled equations of QIA can be reduced to a single equation for complex polarization angle (CPA), which characterizes all the parameters of polarization ellipse. At the same time, the equation for CPA allows obtaining equations for evolution of the traditional parameters of polarization ellipse. Besides, QIA makes it possible to derive in a consistent way Segre’s equation for the Stokes vector evolution, which is widely used in microwave and FIR plasma polarimetry.
Optica Applicata, Vol. 40, 2010, nr 4, s. 975-989
Keywords: optyka; quasi-isotropic approximation; polarization